Turun rannansiirtymisen uudelleenarviointi ja vertailu arkeologisten kaupunkikaivausten dendrokronologiseen ajoitusaineistoon - Jussi Kinnunen (Turun museokeskus, 2022)
Reappraisal of the Shore-Level Displacement and its Comparison of Dendrochronologically Date Wooden Building Materials of the Archaeological Excavations in Medieval Turku Downtown
Shore-level displacement is a commonly used dating method in Finland where land lifting has continued since the last ice age. In the Turku area exists three different shore-level displacement curves. It is noticed that early shore level displacement curves don't match with all archaeologically excavated structure dating. Some structures seem to have been underwater at the time they were constructed.
Contemporary mean water tables are based on very accurate geodetic data, and by using them, it is possible to calculate shore-level displacement about 130 years backwards. Here, three different shore-level displacement curves based on mean water tables were calculated: a) constant curve where shore-level displacement is 3,8 mm/year, b) curve where shore-level displacement is 3,8 mm/year + 1 % retardation/100 years and c) curve where shore-level displacement is 3,8 mm/year + 1,5 % retardation/100 years.
Aboa Vetus & Ars Nova Museum of History and Contemporary Art is situated on the eastern bank of the river Aurajoki. There are several medieval (mainly 15th and 16th century) building remains in the museum, consisting mainly of plaster-walled masonry, quarried dimension stones, natural boulders and bricks. There are also plenty of wooden building remains and altogether about fifty dendrochronologically dated structures.
The main aim of this research was to compare all different early shore displacement curves, curves made backwards in time from contemporary mareograph measurements and dendrochronologically dated structures. It is well-known that shore displacement becomes slower over time, so the constant curve based on mean water tables is the minimum curve for shore displacement.
The main results of this research were:
- The most valid shore-level displacement curve for at least the years 500 BCE – the present in the Turku area seems to be the Vuorela et al. 2009 curve, which is practically identical with the mean water 3,8 mm/year + 1,5 %/100 years -shore-level displacement curve. These two curves are derived using different methods, which supports their validity.
- When estimating subsidence of the soil, it was detected that the medieval city of Turku seems to be founded by a relatively steady, wet, circa 0–20 m thick clay bed, far sturdier than the many other, more strongly sinking areas of Turku.
Pitkin poikin Aurajokea – arkeologisia tutkimuksia